Acraspisoides gen. nov. (Diptera: Therevidae: Agapophytinae): a new genus of stiletto-flies from Australia - Hill, Hilary N.; Winterton, Shaun L. (Zootaxa, 2004)
A new Australian genus of Therevidae, Acraspisoides gen. nov., comprising a single species (A. helviarta sp. nov.) is described and illustrated. This new genus is placed within the subfamily Agapophytinae based on the presence of velutum patches on the fore and hind femora. Acraspisoides is easily separated from other agapophytine genera by the combination of characters: large ventral lobe on aedeagus, multiple rows of postocular setae in both sexes, antennae positioned low on frons, and wing cell m 3 closed. Cladistic analyses using all genera of Agapophytinae (including Acraspisoides) based on adult morphological characters and sequence data of the protein-encoding gene, elongation factor-1 (EF-1a ), were performed to determine the phylogenetic placement of Acraspisoides gen. nov. in the subfamily. Analysis of the combined morphological and molecular matrices produced two most parsimonious trees, placing Acraspisoides gen. nov. as the most basal genus of Agapophytinae.